Self-perceived provision of patient centered care by healthcare professionals: The role of emotional intelligence and general self-efficacy. Issue 5 (May 2017) - Sommaruga, Marinella; Casu, Giulia; Giaquinto, Francesco; Gremigni, Paola
Highlights: Provision of patient-centered care (PCC) within a specific encounter with a patient was self-rated by healthcare professionals. Emotional intelligence (EI) had direct effects on self-perceived provision of PCC. General self-efficacy partially mediated the relationship between EI and patient involvement in care. Rehabilitation professionals perceived themselves as providing more PCC than others healthcare professionals. Abstract: Objective: This study aimed to investigate whether healthcare professionals' emotional intelligence (EI) is associated with self-perceived provision of patient-centered care (PCC), taking into account the potential mediating effect of general self-efficacy (GSE). Methods: A sample of 318 healthcare professionals, recruited in 2015 among four hospitals in Italy, completed the Provider-Patient Relationship Questionnaire, the Emotional Intelligence Scale, and the General Self-Efficacy scale. A structural equation model was tested with GSE mediating the relationship between EI and self-perceived provision of PCC. Groups of participants based on gender, profession, and work setting were also compared on the study variables. Results: EI had direct effects on the self-perceived provision of PCC dimensions. GSE partially mediated only the relationship between EI and involving the patient in care. Healthcare professionals in rehabilitation units showed higher self-perceived provision of PCC than those in acute care or ambulatory services. Conclusion: Self-perceived provision of PCC seems to have the potential to be improved by EI and to be distinguishable from GSE. Practice implications: Since EI can be developed, findings of this study have potential implications for improving PCC through continuing education interventions for healthcare professionals.